Doğadan Toplanan ve Portakal Kütüğünde Yetiştirilen Ganoderma lucidum (Curtis) P. Karst Mantar Türünün Bazı Kimyasal İçeriklerinin Karşılaştırılması - Turfan, Nezahat; Karadeniz, Mertcan; Ünal, Sabri (Turkish Science and Technology Publishing (TURSTEP), 2016)
Ganoderma lucidum (Curtis) P. Karst (Reishi mushroom) is one of medicinal mushroom species. The chemical content of the mushrooms shows significant changes depending on the physical and chemical properties of their growing place. In this study; total soluble protein, total soluble carbohydrate (glucose, fructose and sucrose) and some mineral elements (P, K, Mg, Mn, S, Fe, Zn, Ca and Na) of Ganoderma lucidum collected from the nature and cultured on orange stump were investigated. According to the results; total protein, glucose, fructose, sucrose and starch content of the G. lucidum cultured on orange stump were found higher than G. lucidum collected from nature. Phosphorus, iron, sodium, potassium and sulfur content were determined to be higher in mushroom samples cultured on orange stump. Calcium, magnesium, manganese and zinc values were found as higher in mushroom samples collected from nature. According to these results, G. lucidum cultured on orange stump had higher nutritional value than mushrooms collected from nature.
Keywords: 2. Zero hunger; 15. Life on land; 6. Clean water; 3. Good health